Psychometric properties of the portuguese version of the parental socialization scale in adolescence (ESPA-29) - Nunes, Cristina (2018)
The aim of this study was to validate the Portuguese version of the Parental Socialization Scale in Adolescence (ESPA-29) by Musitu and Garcia (2001, 2004). A sample of 849 adolescents (57.2% girls and 42.8% boys), aged 10 to 18 years (M = 14.57, SD = 2.43), from the southern region of Portugal, participated in the study. Construct validity was studied using exploratory factor analysis, and the reliability study was conducted through the analysis of internal consistency and temporal stability (through the test-retest method). Results were consistent with those obtained in the original version of the instrument and reproduced the bi-dimensional structure of the scale. Furthermore, the Portuguese version of ESPA-29 showed good psychometric characteristics, with satisfactory levels of internal consistency and temporal stability. These results suggest that this is a reliable instrument for studying parental socialization styles in Portuguese adolescents.